MEMANFAATKAN KETERSEDIAAN HIJAUAN PAKAN TERNAK (HPT) DALAM BERBAGAI KOMPOSISI PAKAN UNTUK MENJAGA PRODUKTIVITAS SAPI BALI (STUDI KASUS DI DESA BELANGA, BANGLI) - Suyasa, Nyoman; Budiari, Ni Luh Gede; Parwati, I.A.P (Pastura, 2017)
Livestock development is part of the development of the agricultural sector which has strategic value in meeting the food, especially animal protein is increasing. Agricultural development today has changed from a predominantly supply of carbohydrate to impartial toward providing animal protein. It is also associated with increased per capita income of the people in Indonesia. Cattle is one of the largest providers of animal protein and are ruminants that consume forage such as grass, legume and also leaves from trees. Forage available in the field also depends on the season. The study was conducted in the village of Belanga, Susut, Bangli District, using 13 types of forage in the location. Preparation of rations based on a combination of food resource availability based on the nutritional needs of cattle so that productivity is maintained. The combination of local forage composition from November to April TDN and protein content reached 57.03% and 12.68%, while in May to October TDN and protein reached 57.03% and 12.67%. Key words: forages availability, forage composition, and bali cattle produktivity